2005
DOI: 10.1039/b412532k
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated organic compounds in human blood serum and seminal plasma: a study of urban and rural tea worker populations in Sri Lanka

Abstract: Concentrations and accumulation of 13 fluorinated organic compounds (FOCs) in human sera and seminal plasma were measured in an Asian developing country, Sri Lanka. Six of the FOCs, PFOS (perfluorooctanesulfonate), PFHS (perfluorohexanesulfonate), PFUnA (perfluoroundecanoic acid), PFDA (perfluorodecanoic acid), PFNA (perfluorononanoic acid) and PFOA (perfluorooctanoic acid), were detected in all of the sera samples. Measurable quantities of two main perfluorosulfonates, PFOS and PFHS, were found in all seminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
3
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(97 citation statements)
references
References 28 publications
4
86
3
4
Order By: Relevance
“…Previous studies have reported that PFOA is the PFC that occurred at the second greatest concentrations in human blood (serum and whole blood) samples (12,13,20). However, in the present study, concentrations of PFOA were fourth highest among the PFCs measured.…”
Section: Concentrations Of Pfcs In Blood Samples From Chinacontrasting
confidence: 79%
See 1 more Smart Citation
“…Previous studies have reported that PFOA is the PFC that occurred at the second greatest concentrations in human blood (serum and whole blood) samples (12,13,20). However, in the present study, concentrations of PFOA were fourth highest among the PFCs measured.…”
Section: Concentrations Of Pfcs In Blood Samples From Chinacontrasting
confidence: 79%
“…Our test results showed that the widely used surrogate 13 C-PFOA ( 13 C-PFOA from Perkin-Elmer) contained significant amounts of PFBA and PFPeA. Hence, 13 C-PFOA was used only for checking the overall recovery of target chemicals during the analytical procedure. Due to the problem of contaminants in the standards, recoveries of native chemicals were tested in a series of preliminary experiments instead of using internal standards.…”
Section: Methodsmentioning
confidence: 99%
“…PFOS, PFOA and PFHxS concentrations in human blood (*, serum data, or whole blood data converted to serum basis by multiplying by a factor of 2) of the general population (male adults; except for Sweden: female adults) in several cities all over the world (2000-05); data adapted from references that are cited following the data: China [41] ; USA, Poland, South Korea, Belgium, Malaysia, Brazil, Japan (2002), Colombia, Italy, India [26] ; Canada [160] ; Japan (2003) [138] ; Australia [161] ; Norway [39] ; Sweden [51] ; Germany [162] ; Sri Lanka. [163] Chinese cities no age-related differences were observed. [41] A plausible explanation for this inconsistency is not yet known.…”
Section: Levels and Trends In Humansmentioning
confidence: 85%
“…No statistically significant difference was found in PFCs concentrations between rural and urban regions in an Australia study (Karrman et al, 2006), while higher PFOS and PFOA concentrations in urban areas compared to rural areas could be seen in Japan and Sri Lanka (Harada et al, 2004;Guruge et al, 2005). Another study conducted in Germany reported that PFOA concentrations were significantly decreased in urban populations comparing to populations living in the rural area, but there was no significant difference in PFOS concentrations between urban and rural populations (Fromme et al, 2007).…”
Section: Region Effect On Pfcs Concentrationsmentioning
confidence: 99%